2014
DOI: 10.1111/acem.12408
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Competency Assessment in Emergency Medicine Residency Programs

Abstract: Objectives: In the Model of the Clinical Practice of Emergency Medicine (EM), bedside ultrasound (US) is listed as one of the essential procedural skills. EM milestones released by Accreditation Council for Graduate Medical Education and American Board of Emergency Medicine require residents to demonstrate competency in bedside US. The purpose of this study was to assess the current methods used by EM residency training programs to evaluate resident competency in bedside US.Methods: This was a cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
87
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(89 citation statements)
references
References 8 publications
1
87
0
1
Order By: Relevance
“…A recent study on femoral nerve blocks demonstrated that 63% of emergency medicine attending physicians reported learning US‐guided nerve blocks from a colleague, course, or workshop 23 . Our study indicates that most emergency departments have some form of US‐guided nerve block education, which is consistent with previous literature demonstrating the extent of US training during emergency medicine residency 9 . Although our data show that most (84%) of academic emergency departments use US guidance to perform peripheral nerve blocks, it is unknown whether residents are receiving sufficient exposure to US‐guided nerve blocks to achieve competency.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A recent study on femoral nerve blocks demonstrated that 63% of emergency medicine attending physicians reported learning US‐guided nerve blocks from a colleague, course, or workshop 23 . Our study indicates that most emergency departments have some form of US‐guided nerve block education, which is consistent with previous literature demonstrating the extent of US training during emergency medicine residency 9 . Although our data show that most (84%) of academic emergency departments use US guidance to perform peripheral nerve blocks, it is unknown whether residents are receiving sufficient exposure to US‐guided nerve blocks to achieve competency.…”
Section: Discussionsupporting
confidence: 89%
“…[6][7][8] Due to the mandated point-of-care US training requirements in all emergency medicine residency programs, access to US systems and US education have increased over the past few decades. 9,10 Although the growing body of evidence in the emergency medicine literature demonstrates the utility of US-guided nerve blocks for pain control in various clinical scenarios (laceration repair, incision and drainage, exploration for a foreign body, joint dislocation, and fracture management), it is unknown whether USguided nerve blocks are actively taught and performed in academic emergency medicine training programs. 1,11,12 Knowledge of current practice patterns, emergency department-based collaborations/protocols, and educational pathways could help formulate practice standards for the use of US-guided nerve blocks in emergency medicine.…”
mentioning
confidence: 99%
“…Studies show it to be highly sensitive and specific (88% sensitive and 93% specific) for NF based on certain imaging criteria, such as soft tissue thickening, fascial fluid accumulation greater than 4 mm, and the presence of subcutaneous air [12]. In some cases involving non-gas producing Group A Streptococci infections, ultrasound has been shown to help diagnose NF with negative findings on CT and MRI [6]. Given that NF is rare, difficult to diagnose, and associated with increased mortality with delayed diagnosis, it is imperative that clinicians take immediate action such as promptly initiating surgical consultation when suspecting NF [14].…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Academic Emergency Medicine, Amini et al 1 present the results of a survey of EM residency and US directors to ascertain the current methods of education, quality assurance, and competency assessment in existing US programs. They received surveys from 77% of residency programs, 87% of which have required rotations in emergency US.…”
mentioning
confidence: 99%
“…Although the literature has begun to lay the groundwork for a standardized US curriculum and the development of US assessment tools, Amini et al 1 still describe a very heterogeneous training landscape.…”
mentioning
confidence: 99%